Coordinated Multipoint JCAS in 6G Mobile Networks - Su, Yanpeng; Lübke, Maximilian; Franchi, Norman (IEEE Access, 2024)
Joint communications and sensing (JCAS) is regarded as a key technology of 6G communications since it allows the integration of sensing functions into communications networks with lower hardware costs, less energy consumption, and saved spectrum. As distributed sensing benefits from increased spatial diversity and accuracy, the combination of coordinated multipoint (CoMP) transmission technology and JCAS has become an attractive research direction. CoMP transmission has been applied in 4G and 5G communications networks due to its attractive capability in suppressing inter-cell interference and improving channel capacity, while CoMP sensing and CoMP JCAS have been widely discussed in recent years. However, relevant researches mainly focus on waveform design and optimization issues in the processes of CoMP signal transception and processing, while their system architecture and operation modes are less discussed. To fill the blank in these areas and discuss the benefits provided by CoMP JCAS, in this work, based on the modern CoMP transmission technologies in state-of-the-art mobile network architecture, we analyze the network architecture and required enabler technologies of CoMP JCAS in future mobile networks, focusing on the sensing aspect. In addition, we propose the potential sensing operation and clustering types and discuss their respective advantages and shortcomings. In the simulation, the sensing coverage and accuracy of different CoMP sensing types and conventional standalone sensing are compared. The simulation results show that CoMP sensing outperforms conventional single-radar sensing in accuracy, and the difference between them increases with the distance between the sensors. In addition, it is described that the coordinated passive sensing scheme extends the service area, while the active sensing scheme benefits from higher accuracy with the same bandwidth.<br
Keywords: 6G; B5G; coordinated multipoint (CoMP); cloud radio access network (C-RAN); joint communications and sensing (JCAS); mobile network; networked radar.